Acquired acid resistance of human enamel treated with laser (Er:YAG laser and Co 2 laser) and acidulated phosphate fluoride treatment: An in vitro atomic emission spectrometry analysis - Anju Mathew; N Venugopal Reddy; D K Sugumaran; Joby Peter; M Shameer; Liju Marcely Dauravu (Wolters Kluwer Medknow Publications, 2013)
Background: Dental caries is essentially a process of diffusion and dissolution. If the aspect of dissolution can be curtailed some degree of prevention can be achieved. Aims: The present study was carried out to evaluate and compare the effect of Er:YAG laser and Co 2 laser irradiation combined with acidulated phosphate fluoride treatment on in vitro acid resistance of human enamel. Design: An in vitro study was carried out on 30 human premolars to evaluate the enamel's acid resistance using an atomic emission spectrometry analysis. Materials and Methods: A total of 60 enamel specimens were prepared from 30 human premolars and were randomly assigned to 6 groups: (1) Untreated (control); (2) 1.23% acidulated phosphate fluoride (APF) gel application alone for 4 min; (3) Er:YAG laser treatment alone; (4) Co 2 laser treatment alone; (5) Er:YAG laser + APF gel application; (6) Co 2 laser + APF gel application. The specimens were then individually immersed in 5 ml of acetate buffer solution (0.1 mol/L, pH 4.5) and incubated at 37°C for 24 h, and the acid resistance was evaluated by determining the calcium ion concentration using the atomic emission spectrometry. Statistical Analysis: An ANOVA model was constructed (P value of 0.05), followed by Tukey's test for multiple pair wise comparisons of mean values. Results: Significant differences were found between the control group and the test groups ( P < 0.001). Conclusions: Combining acidulated phosphate fluoride with either Er:YAG or Co 2 laser had a synergistic effect in decreasing the enamel demineralization more than either fluoride treatment or laser treatment alone.